Research 2.0 A Congress Model in the Post-Digital Society - Berlanga Fernández, Inmaculada; Merino Arribas, Adoración (Historia y Comunicación Social, 2014)
The article presents a successful experience of new formats applied to university research: a model of a congress which exploits the possibilities of emerging technologies in the so callled post-digital society. The proposal converts the event into a medium of training for the young researchers with emphasis on the essential role of the chairperson. In this way, the work of the COYSODI research group (Communication and the Digital Society) addresses the multiple aspects of the 100% online education model.
Keywords: communication; academic congresses; online; media literacy; post-digital.